The Concept of Deification in Greek and Syriac - Seppälä, Serafim (Review of ecumenical studies, 2019)
The early patristic authors dealt with the idea of deification in varying circumstances, in relation to different questions, and in more than one language. This article examines Syriac and Greek discourses and vocabularies related to deification in Early Christian and Post-Chalcedonian sources, concentrating on the Syriac tradition, which is less studied. The comparison illustrates certain similarities and differences. The most striking difference is, perhaps surprisingly, that in the Syriac tradition, the idea of deification is prevalent but specific terms to indicate it are almost never used. The incommensurability of the discourses exemplifies the conceptual difficulties at the emergence of the schisms between the Greek and Syriac speaking parts of Christendom.